Application of Mathematics Learning Model Creative Problem Solving that Assisted with Desmos to Improve Students’ Critical Thinking Skills of SMKN 14 Medan - Kristiani Magdalena Simanungkalit; Waminton Rajagukguk (PT FORMOSA CENDEKIA GLOBAL, 2022)
The object of this research is students’ critical thinking skills by applying the Creative Problem Solving (CPS) learning model and is assisted with to material Linear Equation System of Two Variables in class X TPBO of SMK Negeri 14 Medan. The result analysis revealed that: there is improvement of students’ critical thinking skill after applying those action, such as, the observation for students’ critical activities increased from 37,27% in cycle I to 80% in cycle II, with gain index 0,70 (medium), there are 19 out of 31 students (61,29%) have attained the standard of critical thinking skills with mean score 62,60, improved after the execution in cycle II became 27 out of 31 students (87,10%) and mean 81,45, with gain index 0,67 (medium) and the responses of students for interview in cycle II show students’ critical thinking skills in solving the problems.